Receipt of social services intervention in childhood, educational attainment and emergency hospital admissions: longitudinal analyses of national administrative health, social care, and education data in Wales, UK - Emily Lowthian; Graham Moore; Annette Evans; Rebecca Anthony; Muhammad Azizur Rahman; Rhian Daniel; Sinead Brophy; Jonathan Scourfield; Chris Taylor; Shantini Paranjothy; Sara Long (BMC Public Health)
Abstract Background Research consistently finds poorer health and educational outcomes for children who have experienced out-of-home care relative to the general population. Few studies have explored differences between those in care and those in receipt of intervention from social services but not in care. Children receiving social services interventions often experience Adverse Childhood Experiences (ACEs), and deprivation, which are known to negatively impact outcomes. We aimed to estimate the association of different social services interventions with educational outcomes and hospital admissions, while adjusting for ACEs and deprivation. Methods We linked retrospective, routinely collected administrative records from health, education, and social care to create a cohort via the Secure Anonymised Information Linkage (SAIL) databank in Wales, UK. We analysed data for children and household members (N = 30,439) across four different groups: (1) no social care intervention; (2) children in need but not in care (CIN); (3) children on the Child Protection Register but not in care (CPR); (4) children in care - i.e. removed from the family home and looked after by the local authority (CLA). Our primary outcome was education outcomes at age 16 years. Secondary outcomes were all cause emergency hospital admissions, and emergency admissions for external causes/injuries. Results Children in receipt of social services intervention were more likely to not attain the expected level upon leaving statutory education at age 16 after adjusting for ACEs and other characteristics (for children who had been in out-of-home care (conditional OR: 1·76, (95%CI) 1·25 − 2·48), in need (2·51, 2·00–3·15) and those at risk (i.e., on the child protection register) (4·04, 2·44 − 6·68). For all-cause emergency admissions, all social care groups were at greater risk compared to children in the general population (children in care (conditional HR: 1·31, 1·01–1·68), children in need (1·62, 1·38 − 1·90), and children at risk (1·51, 1·11 − 2·04). Conclusions All groups receiving social service intervention experience poorer educational and health outcomes than peers in the general population. Children who remain with their home parents or caregivers but are identified as ‘in need’ or ‘at risk’ by social care practitioners require further research. Integrated support is needed from multiple sectors, including health, educational and social care.